2018
DOI: 10.7150/jca.25469
|View full text |Cite
|
Sign up to set email alerts
|

S100A4-MYH9 Axis Promote Migration and Invasion of Gastric Cancer Cells by Inducing TGF-β-Mediated Epithelial-Mesenchymal Transition

Abstract: Driver genes conducing to peritoneal metastasis in advanced gastric cancer remain to be clarified. S100A4 is suggested to evolve in metastasis of gastrointestinal cancer, we aim to explore the role of S100A4 plays in metastasis of advanced gastric cancer and the potential mechanism. Transfection of siRNA or cDNA was applied to alter the expression of protein S100A4 and MYH9, investigation of the expression of epithelial and mesenchymal transition (EMT) associated markers was followed. Cell migration assay was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…For example, MYH9 overexpression was induced by LIM kinase 1 (LIMK1) and promoted growth and metastasis by activating MAPK/AKT signaling in colorectal cancer 33,34 . The S100A4‐MYH9 axis could promote migration and invasion through inducing transforming growth factor‐β‐mediated epithelial‐mesenchymal transition in gastric cancer 35 . In addition, MYH9 was downregulated by miR‐124, miR‐647, or let‐7f to suppress invasion and metastasis in colorectal or gastric cancer 36‐38 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, MYH9 overexpression was induced by LIM kinase 1 (LIMK1) and promoted growth and metastasis by activating MAPK/AKT signaling in colorectal cancer 33,34 . The S100A4‐MYH9 axis could promote migration and invasion through inducing transforming growth factor‐β‐mediated epithelial‐mesenchymal transition in gastric cancer 35 . In addition, MYH9 was downregulated by miR‐124, miR‐647, or let‐7f to suppress invasion and metastasis in colorectal or gastric cancer 36‐38 .…”
Section: Discussionmentioning
confidence: 99%
“…3 MYH9 is dysregulated and serves as an oncogene in many cancers; [4][5][6][7][8][9][10] however, its expression is positively associated with a good prognosis in patients with head and neck squamous cell carcinomas. 11 Moreover, researchers have reported that MYH9 promotes cell invasion and metastasis in gastric cancer, 12,13 facilitates cell growth and metastasis in colorectal cancer and pancreatic cancer, 14,15 and induces drug resistance in neuroblastoma. 16 However, the role of MYH9 in modulating HCC stemness has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…It suppresses bladder cancer stem cell proliferation by interacting with the IKK/NF-κB signaling pathway [22] . S100A4-MYH9 axis enhance migration and invasion of cancer cells by inducing epithelial-mesenchymal transition in gastric cancer [23] . Here we indicated that S100A4 expression is closely correlated with tumor progression in CRC, and this study is the first report about the role of S100A4 in promoting CRC growth by enhancing glycolysis.…”
Section: Discussionmentioning
confidence: 99%